Australia : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that despite the synchronized slowdown in the rest of the world in 2001, the Australian economy has continued to grow strongly. This performance reflected the absence of major imbalances in the economy, an aggressive easing of monetary policy, fiscal policy stimulus, and a competitive exchange rate. Real GDP has risen at an average annual rate of 3 3/4 percent since end-2000. With underlying inflation pressures muted and the uncertainty about the depth and duration of the global slowdown, monetary policy was highly supportive of growth.